Sound and Power in the Christian Realm of Ethiopia (Seventeenth–Eighteenth Centuries) - Wion, Anais; Damon-Guillot, Anne; Weisser, Stéphanie (Aethiopica, 2017)
Musical instruments were used in the Christian realm of Ethiopia during the early modern period for proclamations, major religious celebrations, court ceremonies, and the movement of the king and his troops inside and outside of royal cities, as well as for signaling the start of battles. Only the powerful had the prerogative of having certain instruments played. The nägarit (kettledrums) were also insignia of power. Owning or displaying them was an expression of power as much as having them played. The nǝsǝr qana were doubel-reed instruments associated with the king. Originally insignia of Oromo military might, the mäläkäts, long trumpets, were gradually adopted in the Christian realm as the Oromo came to share in exercising power. On the basis of evidence drawn from a study of images, horns, though still present on the battlefield, seem to have lost prestige to the benefit of trumpets.